BADAN ARBITRASE NATIONAL DISPUTE RESOLUTION CHAMBER (NDRC) SEBAGAI PENYELESAIAN DALAM WANPRESTASI KONTRAK PEMAIN SEPAK BOLA DI INDONESIA - Yoakim Vocalio Buwana; Adi Sulistiyono (Jurnal Privat Law, 2025)
AbstractThis article aims to analyze the roles of National Dispute Resolution Chamber (NDRC) arbritation body in resolving dispute of football player in Indonesia. This research is normative law research that is prescriptive. The research using primary legal materials and secondary legal materials. Legal material collection techniques using library study techniques through electoral media and then strengthened by interviews. The analysis technique used is an analysis technique with deductive methods. The results of this research show that NDRC is a ray of hope in an attempt to transform Indonesian football into a deeper passion and more professional one. NDRC Indonesia has full authority in resolving disputes of football players in Indonesia, especially disputes that occur due to defaults on their contracts. But in practice in the escort of the verdict has not been affirmed effectively and maximally. There needs to be proper synergy from various stakeholders in an effort to build better Indonesian football.Keywords: Arbritration, Contract, Dispute, NDRC.